A cost-consequence analysis of parecoxib and opioids vs opioids alone for postoperative pain: Chinese perspective - Barra M; Remák E; Liu DD; Xie L; Abraham L; Sadosky AB (Dove Medical Press, 2019)
Magdolna Barra,1 Edit Remák,1 Dong Dong Liu,2 Li Xie,2 Lucy Abraham,3 Alesia B Sadosky4 1Evidera, Budapest, Hungary; 2Health Economics & Outcomes Research, Pfizer Investment Co., Ltd., Beijing, China; 3Health Economics & Outcomes Research, Pfizer Ltd, Tadworth, UK; 4Health Economics & Outcomes Research, Pfizer Inc, New York, NY, USA Purpose: The use of parecoxib plus opioids for postoperative analgesia in noncardiac surgical patients seems to be cost-saving in Europe due to a reduction in opioid use and opioid-related adverse events. Given the lack of information on postoperative analgesic use in Asia, this study assessed the economic consequences of the addition of parecoxib to opioids vs opioids alone to treat postsurgical pain in China.Methods: A cost-consequence economic evaluation assessed direct medical costs related to opioid-related clinically meaningful events (CMEs) utilizing dosing information and reported frequency of events from a Phase III, randomized, double-blind, global clinical trial (PARA-0505-069) of parecoxib plus opioids vs opioids alone for 3 days following major orthopedic, abdominal, gynecologic, or noncardiac thoracic surgery requiring general or regional anesthesia. The cost of CMEs was calculated using information on resource utilization and unit costs provided by a panel of clinical experts in China. Sensitivity analyses were performed to test the robustness of the results.Results: Patients treated with parecoxib plus opioids reported fewer CMEs (mean 0.62 vs 1.04 events per patient [P<0.0001]) compared with opioids alone for the 3-day postoperative period. This suggested a potential savings of 356 Chinese yuan (¥) per patient over the 3 days (total cost of ¥1,418 for parecoxib plus opioids vs ¥1,774 with opioid use alone).Conclusion: Fewer CMEs with parecoxib plus opioids suggest a reduction in medical resource utilization and reduced costs compared to opioids alone when modeling analgesic use in noncardiac surgery patients in China. Keywords: multimodal analgesia, parecoxib, opioids, treatment costs